Effectiveness of Psychosocial-Based Resilience Intervention on Reducing Negative Emotional States among Schizophrenia Caregivers - Valentino Marcel Tahamata; Dian Veronika Sakti Kaloeti (Journal of Educational, Health and Community Psychology, 2020)
Schizophrenia caregivers are chronically exposed to a high level of negative emotional states such as depression, anxiety, and stress. Many studies have explored the problem among caregivers, but there remains to be limited evidence in the use of psychotherapeutic intervention to reduce schizophrenia caregivers’ psychological adversities. This study aims to evaluate the effectiveness of psychosocial-based resilience intervention in reducing the negative emotional states of schizophrenia caregivers. The one group pre-post quasi-experimental design was conducted to five participants. Following the six sessions of training and two-weeks of follow-up, participants showed a significant reduction of negative emotional states (p= .007), measured using the Depression, Anxiety, and Stress Scale (DASS-21). Furthermore, dimensions of negative emotional states were also significantly reduced i.e., depression (p= .008), anxiety (p= .015), and stress (p= .016). These results provide evidence that a psychosocial-based resilience program can effectively reduce the negative emotional states of schizophrenia caregivers.Keywords: Resilience, Depression, Anxiety, Stress, Family Caregiver, Psychosis